The C-terminal p6 domain of the HIV-1 Pr55Gag precursor is required for specific binding to the genomic RNA. Issue 7 (3rd July 2018) - Dubois, Noé; Khoo, Keith K.; Ghossein, Shannon; Seissler, Tanja; Wolff, Philippe; McKinstry, William J.; Mak, Johnson; Paillart, Jean-Christophe; Marquet, Roland; Bernacchi, Serena
ABSTRACT: The Pr55 Gag precursor specifically selects the HIV-1 genomic RNA (gRNA) from a large excess of cellular and partially or fully spliced viral RNAs and drives the virus assembly at the plasma membrane. During these processes, the NC domain of Pr55 Gag interacts with the gRNA, while its C-terminal p6 domain binds cellular and viral factors and orchestrates viral particle release. Gag∆p6 is a truncated form of Pr55 Gag lacking the p6 domain usually used as a default surrogate for wild type Pr55 Gag for in vitro analysis. With recent advance in production of full-length recombinant Pr55 Gag, here, we tested whether the p6 domain also contributes to the RNA binding specificity of Pr55 Gag by systematically comparing binding of Pr55 Gag and Gag∆p6 to a panel of viral and cellular RNAs. Unexpectedly, our fluorescence data reveal that the p6 domain is absolutely required for specific binding of Pr55 Gag to the HIV-1 gRNA. Its deletion resulted not only in a decreased affinity for gRNA, but also in an increased affinity for spliced viral and cellular RNAs. In contrast Gag∆p6 displayed a similar affinity for all tested RNAs. Removal of the C-terminal His-tag from Pr55 Gag and Gag∆p6 uniformly increased the Kd values of the RNA-protein complexes by 2.5 fold but did not affect the binding specificities of these proteins. Altogether, our results demonstrate a novel role of the p6 domain in the specificity of Pr55 Gag -RNA interactions, and strongly suggest that the p6 domain contributes to the discrimination of HIV-1 gRNA from cellular and spliced viral mRNAs, which is necessary for its selective encapsidation.